Tingkat Kepercayaan Diri Akademik Mahasiswa Fakultas Kedokteran Gigi: Studi Pengukuran dengan ABC Test - Ardinansyah, Agus; Akbar, Muhamad F.; Ardy, Okky M.; Sugianto, Irfan (e-GiGi, 2025)
Abstract: Academic success among students is often measured by the achievements they attain; one of which is on-time graduation. One factor that can influence academic achievement is academic self-confidence. The ABC test questionnaire is used to measure academic self-confidence. This study aimed to analyze the differences in academic self-confidence between undergraduate and professional students at the Faculty of Dentistry, Universitas YARSI, using the ABC test. This was a comparative and analytical study with a cross-sectional design. Subjects consisted of 270 students, including both undergraduate and professional students. The results showed that the academic self confidence of undergraduate students was assessed, as follows: very good (55.7%), good (43.5%), and low (0.8%). Meanwhile, academic self-confidence of professional students was assessed as follows: very good (46%), good (53.2%), and low (0.7%). Statistical analysis revealed a significant difference in the academic self-confidence levels between undergraduate and professional students, with a p-value of 0.015. In conclusion, there is a significant difference in the academic self confidence levels between undergraduate and professional students at the Faculty of Dentistry, Universitas YARSI. Keywords: self-confidence; dental education; undergraduate student; professional student; ABC test Abstrak: Keberhasilan akademik mahasiswa sering kali diukur melalui prestasi yang dicapai, salah satunya ialah kelulusan tepat waktu. Salah satu faktor yang memengaruhi prestasi akademik ialah kepercayaan diri akademik. Untuk mengukur tingkat kepercayaan diri akademik, digunakan kuesioner ABC test. Penelitian ini bertujuan untuk menganalisis perbedaan tingkat kepercayaan diri akademik antara mahasiswa tingkat sarjana dan mahasiswa tingkat profesi di Fakultas Kedokteran Gigi Universitas YARSI, dengan menggunakan ABC test. Jenis penelitian ini ialah analitik komparatif dengan desain potong lintang. Subjek penelitian terdiri dari 270 mahasiswa, yang terdiri dari mahasiswa tingkat sarjana dan mahasiswa tingkat profesi. Hasil penelitian menunjukkan bahwa mahasiswa tingkat sarjana memiliki penilaian kepercayaan diri akademik sangat baik (55,7%), baik (43,5%), dan rendah (0,8%). Mahasiswa tingkat profesi memiliki penilaian kepercayaan diri akademik sangat baik (46%), baik (53,2%), dan rendah (0,7%). Analisis statistik menunjukkan adanya perbedaan bermakna antara tingkat kepercayaan diri akademik mahasiswa tingkat sarjana dan mahasiswa tingkat profesi, dengan nilai p=0,015. Simpulan penelitian ini ialah terdapat perbedaan bermakna antara tingkat kepercayaan diri akademik mahasiswa tingkat sarjana dan mahasiswa tingkat profesi di Fakultas Kedokteran Gigi Universitas YARSI. Kata kunci: kepercayaan diri; pendidikan kedokteran gigi; mahasiswa sarjana; mahasiswa profesi; ABC test